Effective Models of Teaching and Learning for New Type of Students - Mustapha, Ramlee (ASPENSI, 2011)
ABSTRACT: Educators are faced with the challenge of adapting their teaching styles to accommodate a new generation of digital learners. These digital learners, who are now entering colleges and universities, have learning expectations, styles, and needs different from past students. The question is how to adapt teaching strategies to accommodate the digital learners, in light of their preferences for digital literacy, experiential learning, interactivity, and immediacy? Meanwhile, the higher education today has also the opportunity to reshape itself and play an important role in the future of our society. Whether that role is ultimately fulfilled will depend on fresh, creative thinking, and a firm commitment to move teaching, learning, and the university into the digital age. The manner in which students are taught will not truly change until the manner in which we teach and evaluate students change. This working paper tries to elaborate the multiple studies that suggest moving students from consumers of information to producers of information. This is the key to engaging digital learning. However, until teachers are trained to expect and accept content gathered through social networks with emphasis on teaching students how to check validity and reliability of the web, the full power of the digital natives can not be released or expanded. Finally, this working paper recommends that teachers must allow students to publish broadly then promote peer and expert outside evaluation. These new learners are instructed by teachers who, for the majority, spent childhoods engulfed in television programs that fed information for consumption, rather than interaction, omitting the choices and short snippets that lead to further discovery. KEY WORD: Teaching and learning styles, digital era, higher education roles, and digital capabilities of teacher and student.About the Author: Prof. Dr. Ramlee Mustapha is Dean of Institute for Post-Graduate Studies UPSI (Sultan Idris University of Education), 35900 Tanjong Malim, Perak Darul Ridzuan, Malaysia. He can be reached at: drramlee@yahoo.comHow to cite this article? Mustapha, Ramlee. (2011). âEffective Models of Teaching and Learning for New Type of Studentsâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.1(1) Juni, pp.1-26. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, ISSN 2088-1290.Chronicle of the article: Accepted (April 28, 2011); Revised (May 20, 2011); and Published (June 5, 2011).